Freshwater management - Ramesh, R.; Ramachandran, S. (New Delhi : Capital Pub. Co., 2005)
Contributed papers presented at the International Conference on Coastal and Freshwater Issues, held at Institute for Ocean Management, Anna University, Chennai, during December 8-10, 2003.
Keywords: Freshwater ecology -- Congresses; Water quality -- Congresses; Ecosystem management -- Congresses